Cutaneous manifestations of coronavirus disease in Turkey: A prospective study - Yeniay Yildiray; Pekdemir Sen Ayse (Wolters Kluwer Medknow Publications, 2021)
Background: Although the clinical features of coronavirus disease 2019 (COVID-19) infection are mainly based on respiratory system symptoms, different types of skin manifestations have been described in the literature. Objectives: We investigated COVID-19 cases in Kocaeli, Turkey, in a period of 3 months to identify and figure out the real burden of skin lesions associated with COVID-19 infection. Methods: A total of 266 patients who had positive results on reverse transcription-polymerase chain reaction analysis of nasopharyngeal swab for severe acute respiratory syndrome coronavirus type 2 between March 2020 and June 2020 at our region were investigated for the study. Results: A total of 266 patients was included in this study, 92 (34.6%) patients were male and 174 (65.4%) were female. The mean ± standard deviation age of the patients was 49.2 ± 18.69 (range: 18-96 years). During clinical examination, 5 (1.9%) patients demonstrated skin lesions that might be associated with COVID-19 infection. These lesions consisted of urticaria in three patients and vesicular eruption in two patients. Conclusion: Although the incidence of cutaneous manifestations was lower than expected, these symptoms are valuable clues to identify patients or asymptomatic individuals in high-risk populations. Further prospective studies in larger populations are needed to better define the real cutaneous aspect of the disease.